Near-infrared absorbing glazing for energy-efficient windows: A critical review and performance assessments from the building requirements - Pu, Jihong; Shen, Chao; Wang, Julian; Zhang, Yingbo; Zhang, Chunxiao; Kalogirou, Soteris A. (My University, 2023)
In the past decades, spectrally selective windows, such near-infrared absorbing (NIR) glazings, low-e glazings, and various smart windows, have been widely studied, developed, and applied in different climatic conditions for building energy-saving purposes. One major pathway of the spectrally selective glazings to achieve energy savings is through solar radiation control, either by NIR reflection or absorption. This review concerns the NIR absorbing glazings with the limited subset of ion-based and nanoparticle-based glazings. In detail, each category's spectral absorbing materials are further distinguished into sub-categories, and then their underlying mechanisms of spectral selectivity were elaborated, as well as their application status in terms of manufacturing, cost, and commercialization popularity. To further advise the application in the building sector, we comparatively evaluated the performance of each kind of glazing in terms of the light and heat decoupling ability and visual qualities (i.e., color rendering). Finally, the challenges and future directions of the NIR absorbing glazings to bridge the gap between lab research and large-scale practical applications are illustrated.
Keywords: Spectrally selective windows; Architectural glazing; Energy saving; Metallic ions; Nanoparticles